An Essay on Welfare State Dynamics - Assar Lindbeck (The Research Institute of Industrial Economics (IUI), 2003)
The expansion of welfare-state arrangements is seen as the result of dynamic interaction between market behaviour and political behaviour, often with considerable time lags, sometimes generating either virtuous or vicious circles. Such interaction may also involve induced (endogenous) changes in social norms and political preferences. Moreover, the internationalisation process not only limits the ability of national governments to redistribute income; they also increase the political demands for international mobility of welfare-state benefits and social services. I also discuss the dynamics of reforms and retreats of welfare-state arrangements.
Keywords: H10; H50; 330; Welfare State; Welfare-State Dynamics; Political Equilibrium; Social Norms; Sozialstaat; Neue politische Ökonomie; Soziale Werte; Sozialreform; Theorie; Soziale Norm